A Novel QoS-Based Framework for Cloud Computing Service Provider Selection - Salama, Maria (2014)
Cloud Computing is a promising computing paradigm that provides flexible, Internet-accessible resources allocation on demand on a pay-as-you-go basis. With the growth and expansion of Cloud services and participation of various services providers, the description of quality parameters and measurement units started to diverse and sometimes contradict. Such ambiguity does not only result in the raise of various QoS interoperability problems, but also in the distraction of the services consumers who find themselves unable to match their quality requirements with the providers' offerings. Influenced by such diversity, the available QoS models are limited to either cost-benefit analysis or performance evaluation, without being able to cover a comprehensive set of well-defined quality aspects. In this paper, we provide a complete framework for such problem. We firstly propose a novel QoS ontology that combine and define all of the existing quality aspects in a unified way to efficiently overcome all existing diversity. Using such ontology, we propose a comprehensive broad QoS model combining all quality parameters of both service providers and consumers for different Cloud platforms. We then propose a mathematical model addressing the Cloud Computing service provider selection optimization problem based on QoS-guarantee. The proposed model reports an efficient matching with the market-oriented different platforms characteristics; validated through extensive simulation studies conducted on benchmark data of Content Delivery Network providers.